Community participation in the Equality Education Program at PKBN Sultan Thaha Saipudin, Tebo Regency - Yunisri, Yunisri; Hiryanto, Hiryanto; Hermawan, Yudan (Universitas Negeri Yogyakarta, 2025)
The equality education program is one of the important efforts to increase access to education for people who cannot participate in formal education. In Tebo Regency, especially in PKBM Sultan Thaha Saipudin, community participation plays a strategic role in the success of this program. However, community involvement in various aspects of implementation still needs to be increased so that the goal of equality education can be achieved optimally. This research aims to identify forms of community participation in equality education programs and government strategies in supporting their implementation. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. Data were analyzed descriptively to illustrate the overall form of community participation and government support. The results of the study show that community participation in PKBM Sultan Thaha Saipudin is not only in the form of financial support, but also in the form of providing facilities and infrastructure, taking advantage of programs, and providing constructive ideas and suggestions. The Aburan Batang Tebo Village Government actively allocates a budget for skills training and business capital for the community that participates in the program. In addition, cooperation with the Education Office, the PMD Office, and the business and industry world provides significant technical training and support. Synergy between village governments, private partners, and communities is the key to increasing the active participation and success of equality education programs, which has a positive impact on improving the welfare of local residents